Investigating Rape Culture in News Coverage of the Anita Hill and Christine Blasey Ford Cases - Blumell, Lindsey E. (Violence against women, 2022)
This content analysis (N = 1,527) examined the presence of rape culture acceptance (dismissal of event, victim blaming, discrediting survivor, and threats to survivor) and anti-rape culture (support for survivor, and mention of: systemic problem, rape culture, and male power dominance) in news coverage of Anita Hill and Christine Blasey Ford’s testimony against a U.S. Supreme Court nominee. Results show higher rape acceptance in Blasey Ford news coverage and no difference between the cases and anti-rape culture. Online news media focused on personal impact to Blasey Ford, while traditional news media focused on impact to Thomas Kavanaugh and Clarence Thomas.